2009
DOI: 10.1007/s10165-009-0192-y
|View full text |Cite
|
Sign up to set email alerts
|

Lupus erythematosus tumidus in Japan: a case report and a review of the literature

Abstract: We report here the case of a 48-year-old Japanese woman showing plaque-forming scattered indurative papules on her face, buttock and extremities. Histological examination revealed a large amount of interstitial mucin deposition, and negative direct immunofluorescence was observed. The provocative phototesting reproduced the skin lesion, and the patient was diagnosed with lupus erythematosus tumidus (LET). A review of ten LET cases previously reported in Japan revealed that all of these cases had clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Concerning LET, DIF was positive in 64% of patients and in all these cases IgM or IgG and/or C3 were present at the DEJ suggesting that immunoglobulins and complement have a more prominent role in mediating the tissue damage than in REM. In the literature, DIF positivity in LET varies according to the different studies: a German study indicates a positivity in about a quarter of patients, while a Japanese study found a positivity in up to 50% . In one LET patient we could find IgG deposits on the DEJ, a finding that has never been reported for REM.…”
Section: Discussionmentioning
confidence: 70%
“…Concerning LET, DIF was positive in 64% of patients and in all these cases IgM or IgG and/or C3 were present at the DEJ suggesting that immunoglobulins and complement have a more prominent role in mediating the tissue damage than in REM. In the literature, DIF positivity in LET varies according to the different studies: a German study indicates a positivity in about a quarter of patients, while a Japanese study found a positivity in up to 50% . In one LET patient we could find IgG deposits on the DEJ, a finding that has never been reported for REM.…”
Section: Discussionmentioning
confidence: 70%